Development of Village Websites to Improve Public Service Quality in Sulangai Village, Badung - amoi, Amoi Rosita Dewi; Nyoman Diah Utari Dewi; Ida Ayu Putu Sri Widnyani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
One of the government regulations that supports the e-government program is presidential instruction no. 3. 2003 concerning National Policy and Strategy for the E-Government Development Program, where this policy was the first regulation established to support the development and implementation of e-government in Indonesia. Sulangai Village is a village located in Petang District, Badung Regency, Bali Province. This village is known for its pristine natural beauty and has great potential in the agricultural and tourism sectors. Local village governments continue to improve their public services by using information technology. One way they do this is by building a village website. In this research, researchers used descriptive qualitative methods, where the type of research is used to provide a clear and in-depth picture of certain situations or conditions based on empirical data. This scientific study uses in-depth observational research methods on research objects, namely the Sulangai Village government website and literature study. Relevant data is collected from books, journals, research reports and other relevant documents. From the results of this research, it was found that the development of a village website in Sulangai Village, Badung, has had a positive impact in improving the quality of public services and strengthening relations between the village government and the community. Through the village website, accessibility of information regarding village government activities, public services and the latest news becomes easier for the community